Persepsi Label Generasi Strawberry dan Career Adaptability pada Job hopping Generasi Z - Luqyana Marsha Firdaus; Amanda Pasca Rini; Nindia Pratitis (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2026)
Generation Z faces a fast and flexible work environment that increases job hopping tendencies. This phenomenon is often linked to perceptions of the strawberry generation label and career adaptability. This study aimed to examine the relationship between these variables and job hopping among Generation Z. A quantitative correlational design with multiple regression analysis was conducted on working Generation Z selected through purposive sampling. Data were collected using scales of strawberry generation label perception, career adaptability, and job hopping. The results showed that simultaneously, both variables were not significantly related to job hopping. However, partially, perceptions of the strawberry generation label were significantly related, while career adaptability was not. These findings highlight the role of generational label perceptions in job hopping tendencies among Generation Z. Keywords: career adaptability; generation Z; job hopping; perception of the strawberry generation label Generasi Z menghadapi dinamika dunia kerja yang cepat dan fleksibel sehingga meningkatkan kecenderungan job hopping. Fenomena ini sering dikaitkan dengan persepsi atas label generasi strawberry dan adaptabilitas karier. Penelitian ini bertujuan mengkaji hubungan kedua variabel tersebut dengan job hopping pada Generasi Z. Penelitian menggunakan pendekatan kuantitatif korelasional dengan analisis regresi berganda pada pekerja Generasi Z yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan skala persepsi generasi strawberry, adaptabilitas karier, dan job hopping. Hasil menunjukkan bahwa secara simultan kedua variabel tidak berhubungan signifikan dengan job hopping. Namun, secara parsial persepsi atas label generasi strawberry berhubungan signifikan, sedangkan adaptabilitas karier tidak. Temuan ini menegaskan peran persepsi label generasi dalam kecenderungan job hopping Generasi Z. Kata kunci: adaptabilitas karier; generasi Z; job hopping; persepsi atas label generasi strawberry